Upaya Mewujudkan Manajemen Perguruan Tinggi yang Efisien dalam Menghadapi Tantangan Global - Syahwalan Syahwalan; Nasrudin Harahap; Nurul Hidayati Murtafiah (Journal on Education, 2023)
The motivation behind this exploration is to analyze Endeavors to Acknowledge Productive Advanced education The executives in Confronting Worldwide Difficulties. The technique utilized in dissecting this issue is a writing concentrate on Endeavors to Acknowledge Productive Advanced education The executives in Confronting Worldwide Difficulties. The consequences of the review show that by being perceptive in confronting worldwide difficulties and endeavors to acknowledge proficient advanced education the board, it is trusted that this will support the progress of the significant jobs of advanced education today, including: First, produce graduates who are reasonable , subjectively and quantitatively with the requirements of society Second, planning an educational program in light of genuine capability needs and educating and growing experiences, which are taken care of by an adequate number of value teachers, suitable hardware and pertinent learning assets in view of the climate and IT. the executives/organization as well as bookkeeping and business venture beyond what many would consider possible. Fourth, planning a framework hierarchical design, "level", lessening the progressive stepping stool to a base, stressing the association of capabilities, yet as an association in light of the rule of family relationship. Making an authoritative culture open to restoration, regarding input. Fifth, saving and taking advantage of instructive money sources as well as fostering the possibility to investigate expansive and strong advanced education subsidizing sources.